DISCIPLINE STYLES AS CORRELATES OF LEARNERS’ SOCIO-EMOTIONAL STABILITY: IMPLICATIONS FOR NON-FORMAL EDUCATION PROVISIONS - Yusuf, Murtala Akanbi; Sani, Musa; Mkpa, Iquo Okon (Indonesian Journal of Elementary Teachers Education, 2024)
There has been a concern that discipline styles adopted by the teachers may have far reaching effect on the emotions of their learners with its consequences on teaching and learning. This study examined school discipline styles as correlates of learners’ socio-emotional stability in primary schools in Tsafe local government area of Zamfara state Nigeria. Three null hypotheses were formulated to guide the study. Corelational survey research design was used for the study. The population of the study was 50160 pupils and 841 primary school teachers. The sample size was 400 pupils and 200 teachers using stratified sampling techniques under Yaro Yamane’s formula. The instruments used for data collection were Questionnaire tagged School Discipline Style Questionnaire (SDQ) and Socio-emotional Scale (SeS). The instruments were validated by the experts. The reliability of the instruments was ascertained using Chronbarch alpha which yielded coefficient indexes of 0.6051 and 0.6040 respectively. Pearson Product-Moment Correlation Coefficient (PPMCC) statistic was used in testing all the null hypotheses at 0.05 level of significance.  The study revealed that authoritarian and laissez faire styles of discipline are detrimental to socio-emotional stability of pupils in Tasfe LGA, Zamfara state while democratic discipline style promotes socio-emotional stability of pupils in primary schools in Tasfe LGA, Zamfara state. It was recommended that, the school authorities should allocate quality time to both pupils and teachers on discipline as education is more of discipline than academic excellence. And explore the potentials of adult and non-formal education such as workshop, campaign and public talk for the use of democratic style and against authoritarian and laissez faire discipline styles.Keyword: discipline styles; socio-emotional stability; non-formal education